Implementation of vector moving Preisach model using texture coefficients as easy axis distribution - Seol, SC; Kang, T; Shin, KH; Lee, TD; Park, GS (AMER INST PHYSICS, 1997)
Vector moving Preisach model was applied to the untextured Co thin film media. The out-of-plane easy axis distribution of the particles was derived directly from the texture coefficient P-hkl obtained from x-ray diffraction analysis, which corresponds to the fraction of the grains that have {hkl} plane lying parallel to in-plane direction. In order to validate this variable, angular dependence of magnetic properties of CoCrPPt/Cr/glass thin films with two different composition was measured by using a vibrating-sample magnetometer. Simulated results showed little difference from the measured data. (C) 1997 American Institute of Physics.